1999
DOI: 10.1046/j.1365-2141.1999.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of 2‐chlorodeoxyadenosine in the treatment of patients with refractory angioimmunoblastic lymphadenopathy with dysproteinemia

Abstract: Summary. Treatment of patients with angioimmunoblastic lymphadenopathy with dysproteinaemia (AILD) often constitutes a challenge for the clinical haematologist. Singleagent and combination chemotherapy have failed to increase the response rate or survival of patients with AILD. A total of seven patients with refractory or relapsed AILD were treated with 2-chlorodeoxyadenosine (2-CdA) for variable number of cycles. The overall response rate was 57% with two patients (28·5%) achieving complete and sustained resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 11 publications
1
10
0
2
Order By: Relevance
“…Sallah et al reported an overall response rate of 60% with a 20% CR rate; our previous reports demonstrated a 70% overall response rate with a CR rate of 11%. 13,14 These findings led us to conclude that gemcitabine has the highest activity with acceptable toxicity in previously treated patients with CTCL. For this reason, we decided to use gemcitabine as the frontline treatment of CTCL to evaluate tumor response, as well as the safety and duration of response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sallah et al reported an overall response rate of 60% with a 20% CR rate; our previous reports demonstrated a 70% overall response rate with a CR rate of 11%. 13,14 These findings led us to conclude that gemcitabine has the highest activity with acceptable toxicity in previously treated patients with CTCL. For this reason, we decided to use gemcitabine as the frontline treatment of CTCL to evaluate tumor response, as well as the safety and duration of response.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported satisfactory results using purine analogs in the treatment of different types of recurrent or refractory T-cell malignancies. 14,23,24 Kurzrock et al reported results using pentostatin in 28 CTCL patients; the overall response rate was 71% and the most common side effects were granulocytopenia, nausea, and nonneutropenic fever. 25 Other studies examining cladribine, fludarabine, and gemcitabine as single agents in pretreated CTCL patients reported an overall response rate of 24 -47% for cladribine and fludarabine.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous treatments have some efficacy in the management of AITL, but to date there is no consensus about which regimen is best. Because of unsatisfactory results with standard therapy, numerous small studies with mixed results have explored treating AITL with alternative agents such as cyclosporine [17], fludarabine [18], cladribine [19], alemtuzumab [20], methotrexate [21], and thalidomide [22]. Some studies have shown that AITL can be effectively treated with high-dose chemotherapy followed by autologous HSCT [23].…”
Section: To the Editormentioning
confidence: 99%
“…Mortality has been reported as high as 60%, usually due to infections despite treatment with chemotherapy regimens. [27][28][29][30] The etiology of the AILD is unknown. Association with previous medications such as antibiotics and anticonvulsants and viral infections has been reported.…”
Section: Clinical Presentationmentioning
confidence: 99%